Lack of effect of peritubular protein on passive NaCl transport in the rabbit proximal tubule. - Berry, C A (1983)
The effect of peritubular protein removal on passive NaCl transport was examined in the isolated rabbit proximal convoluted tubule (PCT). Three modes of passive NaCl transport were tested: (a) paracellular backflux of NaCl, (b) convective flow of NaCl through junctional complexes, and (c) anion gradient-dependent NaCl transport. The effect of peritubular protein removal on the paracellular permeability to NaCl was examined using transepithelial specific resistance. Eight PCT were perfused with ultrafiltrate (UF) and bathed in either serum or UF. Transepithelial specific resistance averaged 14.5 +/- 1.9 in the presence and 13.7 +/- 1.7 omega cm2 in the absence of peritubular protein. The effect of peritubular protein removal on the convective flow of a NaCl solution across functional complexes was examined in the absence of active transport by using colloid osmotic pressure (COP) gradients. 12 PCT were perfused with simple salt solutions in Donnan equilibrium with and without protein at 20 degrees C. A COP gradient of 60.1 and -60.1 mmHg drove only 0.06 and -0.23 nl/min, respectively. These values are approximately 10% of the value predicted for an effect of peritubular protein on NaCl solution flow (1.98 nl/min) and are approximately equal to the value predicted for pure water equilibration for the small osmotic pressure difference between solutions in Donnan equilibrium (0.17-0.18 nl/min). The effect of peritubular protein removal on the passive absorption of NaCl driven by anion concentration gradients was examined in seven PCT perfused with a high chloride solution simulating late proximal tubular fluid and bathed in either serum or UF at 20 degrees C. Volume absorption averaged 0.34 +/- 0.20 in the presence and 0.39 +/- 0.20 nl/mm min in the absence of peritubular protein. In conclusion, peritubular protein removal did not significantly affect any of the three distinct modes of passive NaCl transport tested. The lack of effect of peritubular protein removal on passive paracellular NaCl transport suggests that protein modulates an active transcellular NaCl transport process.